Effect of Additive Elements (x = Cr, Mn, Zn, Sn) on the Phase Evolution and Thermodynamic Complexity of AlCuSiFe-x High Entropy Alloys Fabricated via Powder Metallurgy - Sharma, Ashutosh; Lee, Hansung; Ahn, Byungmin (Metals and Materials International, 2022)
In this study, equimolar AlCuSiFe-x (x = Cr, Mn, Zn, Sn) HEAs were fabricated by mechanical alloying (MA) and spark plasma sintering methods (SPS). The MA was performed for 45 h followed by densification of powder compacts at 650 °C. The results revealed the formation of dual face-centered cubic (FCC) and body-centered cubic (BCC) structures in AlCuSiFe-x (x = Zn, Sn) while a single BCC solid solution was noticed in AlCuSiFe-x (x = Cr, Mn). After SPS treatment, AlCuSiFeSn alloy contained FCC with CuxSny while AlCuSiFe–Zn changed to FCC + BCC structure. Similarly, AlCuSiFeCr and AlCuSiFeMn showed the formation of BCC + FCC with additional σ- and µ-phases in the HEA matrix. The calculated thermodynamic parameters of HEAs also supported the formation of different solid-solution phases in each of the above HEAs. It was found that HEAs with the additive elements Sn and Zn tend to have major FCC phases, while those with Cr and Mn give rise to major BCC with brittle σ- and µ-phase, which further improves their mechanical strength. Graphic Abstract: [Figure not available: see fulltext.].
Keywords: Additive elements; Body-centred cubic; Cubic solid solutions; Cubic structure; Densifications; Face-centred cubic; High entropy alloys; Phase evolutions; Powder compacts; Spark plasma sintering method; High entropy alloy; Phase evolution; Powder metallurgy; Thermodynamics